A STUDY ON MONOGENEAN PARASITES OF MARINE FISH LUTJANUS JOHNI AND JOHNIUS ANEUS FROM VISAKHAPATNAM COAST, INDIA - SOWJANYA, P.; LAKSHMI, K. VIJAY; ULU, K. SREE RAM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
From species of monogenes were obtained during a survey of metazoan parasites from Lzajamis ohnfi and Johnius aneus off Visakhapatnum coast. Of these fouir species Ancyrocephalus tnanilensis Tubangui, 1931 and Microcotyle polvnemi MacCallum, 1917 are from L. johni and Dip1oslamenides oc/ospines Unnithan, 197i and Lintaxine cokeri (Linton, 1940) Sporoston, 1946 are from J. towns.